AGENESIS OF THE INTERNAL CAROTID ARTERY - COLLATERAL VASCULARIZATION AND SYMPTOMATIC MANIFESTATIONS - Hubert Stachowicz; Karolina Paterek; Aleksandra Makarewicz; Aleksandra Pacek; Joanna Mazurek; Wojciech Gąska; Maciej Samczuk (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and objective: Internal carotid artery agenesis is a rare anatomical anomaly involving the absence of the internal carotid artery. It is a congenital developmental defect that can present with varying symptoms depending on whether it is unilateral or bilateral. The aim of this article is to summarize the diversity and prevalence of symptoms associated with unilateral or bilateral agenesis of the internal carotid artery. Methodology: In the literature review, scientific works related to internal carotid artery agenesis were utilized, including 26 studies addressing the described variability, which collectively encompass 52 cases of patients with internal carotid artery agenesis. After a thorough analysis of the cited literature, conclusions were drawn regarding the frequency and relationships between unilateral and bilateral absence of the ICA. Discussion: Agenesis of the internal carotid artery is a rare anomaly; however, its detection is crucial in the diagnosis of cerebrovascular disorders. Among symptomatic patients with internal carotid artery agenesis, intracranial aneurysms leading to subarachnoid hemorrhages were frequently observed. Additionally, collateral pathways replacing its blood flow, such as perineural anastomoses, and alterations in the normal course of other vessels in the neck and head region were also noted. Conclusions: Agenesis of the ICA occurs in 0.01% of cases and is additionally associated with the absence of the carotid canal, through which the artery typically traverses. It is more commonly seen as left-sided agenesis of the ICA, with bilateral agenesis occurring in less than 10% of cases. 25% of cases of internal carotid artery agenesis are associated with intracranial aneurysms. The majority of symptomatic patients are between 35 and 65 years of age. Patients with internal carotid artery agenesis most frequently exhibit neurological disorders as well as nonspecific symptoms such as headaches and nausea.